SOCIOLOGY LEARNING MODULE BASED ON LOCAL WISDOM TO STRENGTHEN SCHOOL CULTURE: A QUALITATIVE STUDY FROM THE SOCIOLOGY PERSPECTIVE - Ibrahim, Ibrahim; Kamaruddin, Syamsu A; Majid, Abdul; Leesen, Adul (Universitas Labuhanbatu, 2025)
Purpose – This study aims to develop a sociology learning module based on Bugis–Makassar local wisdom to strengthen school culture and internalize cultural values among eleventh-grade students at Madrasah Aliyah Swasta DDI Baru-Baru Tanga, Pangkep. The research addresses instructional limitations in existing materials that lack contextualization, cultural relevance, and the integration of local wisdom into sociology learning.Methodology – The study employed a qualitative development approach, utilizing Borg & Gall's (1983) model, which encompassed needs analysis, module planning, expert validation, revision, and limited field testing. Thirty students participated in the module trial. Data were collected through questionnaires, observations, and interviews, then analyzed descriptively to assess clarity, content relevance, cultural integration, student engagement, and value internalization.Findings – The module was found to be clear, systematic, and easy to understand (average score 4.3). It successfully links sociological concepts with students’ prior knowledge and daily experiences (4.1), integrates key Bugis–Makassar values such as siri’ na pacce, sipakatau, and getteng (4.5), encourages active participation (4.2), and supports the internalization of character-based cultural values (4.0). Overall, the module bridges abstract sociological theory with students' socio-cultural realities while reinforcing school culture and social character.Contribution – This study contributes to the development of culturally integrated and contextually relevant sociology learning materials. The module functions not only as an academic resource but also as a medium for character education rooted in local wisdom. It further demonstrates the effectiveness of the Borg & Gall model in producing high-quality instructional materials suited to students’ cultural contexts.